LEADERSHIP MINDSET DALAM SUMBER DAYA MANUSIA DI ERA VUCA: (Studi kasus pada pola pikir pemimpin di Kabupaten Bojonegoro) - Rosa Putri Nurhalisa; Septi Wulandari; Ida Swasanti (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This study aims to determine and describe how the leadership mindset or mindset of a leader in managing human resources in the VUCA era, especially for leaders in Bojonegoro Regency. This kind of study uses a qualitative approach and is descriptive in design. The government, education, business, entrepreneurial, and community sectors provide the informants for this study. Purposive sampling was used to identify the informants based on pre-established criteria. The following components influence the practice of transformational leadership are idealized influence, individualized consideration, intellectual stimulation, and inspirational motivation.In this study, data were obtained from observations and interviews with predetermined informants. The data analysis technique used is data triangulation. The results of this study indicate that the transformational leadership style mindset is used by leaders who are informants in this study. The model of transformational leadership is thought to be able to overcome the difficulties presented by the VUCA era by fostering a sense of unity, fostering creativity, and fortifying a common vision. In the face of the VUCA era's transformations, organizations that apply a leadership style that emphasizes transformation are also more capable to be innovative and adaptive.